Skin tests in the work‐up of cutaneous adverse drug reactions: A review and update - Barbaud, Annick; Castagna, Julie; Soria, Angèle (Contact dermatitis, 2022)
Skin tests, including patch tests (PTs), prick tests, and intradermal tests (IDTs), are useful in identifying the culprits of cutaneous adverse drug reactions (CADRs), and determining safer, alternative drugs. PTs have a low sensitivity but are valuable in investigating maculopapular exanthema (MPE), as well as severe CADR, including toxic epidermal necrolysis (TEN), Stevens‐Johnson syndrome (SJS), and in particular, acute generalized exanthematous pustulosis (AGEP), and drug reaction with eosinophilia and systemic symptoms (DRESS). To ensure their specificity, at least 10 control tests should be performed. Prick tests are mainly used in the evaluation of immediate‐type hypersensitivity and can be performed with all drugs, except opiates. IDTs can be used to explore immediate and delayed‐type hypersensitivity, if an injectable form of the drug exists. Except for SJS/TEN, IDTs should be performed by injecting 0.02 mL of the drug. We here provide a practical, up‐to‐date review on the use of these skin tests in the work‐up of CADRs. Numerous negative controls for drug PTs, as well as criteria for the immediate and delayed positivity of prick tests and IDT, are included. It should be emphasized that a negative result never excludes the potential responsibility of a drug in a CADR.